Tissue differentiation by means of high resolution optical emission spectroscopy during electrosurgical intervention. (9th December 2016) - Bürger, Ines; Scharpf, Marcus; Hennenlotter, Jörg; Nüßle, Daniela; Spether, Dominik; Neugebauer, Alexander; Bibinov, Nikita; Stenzl, Arnulf; Fend, Falko; Enderle, Markus; Awakowicz, Peter
Abstract: Electrosurgery is the use of radio-frequency electric current for the cutting of biological tissue e.g. for resection of tumour tissue. In this work, the optical emission of plasma being generated during the electrosurgical procedure is investigated with a high resolution echelle spectrometer to find differences between tumour tissue and normal renal tissue in a pre-clinical ex vivo study. Trace elements like zinc, iron, copper and cadmium are present in the tissue spectra as well as the electrolytes magnesium, calcium, sodium and potassium and some diatomic molecules such as hydroxyl radical, cyano radical, dicarbon, nitrogen monohydride and molecular nitrogen which are mainly dissociated from polyatomic molecules. With the atomic emission line of cadmium at 228.8 nm the treated tissue can be differentiated in tumorous and healthy tissue with correct assignment of 95% for tumour tissue and 92% for normal renal tissue.